(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
In this article we intend to analyze the different considerations that Walter Benjamin carried out in his work on the problem of critique as an eminently philosophical subject. To do this, we will address, first, his approach to German romantic poetry, then baroque poetry and, finally, Baudelaire’s work, in order to explain how a full comprehension of critique means, for the German philosopher, to recover the idea of “actualization” as a key for reading History. In fact, if the actualization presupposes, for Benjamin, the assumption of the non-coincidence of time with itself, that is, the survival of the past within the present and its potentiality to signify, we try to show how Benjamin’s notion of criticism rests on that temporal difference and finds there its source of meaning.